ทัศนคติของชุมชนต่อการพัฒนาการท่องเที่ยวภายในพื้นที่ป่าสงวนแห่งชาติ ป่าวังน้ำเขียว-ป่าเขาภูหลวง จังหวัดนครราชสีมา: Attitude of the Community to the Tourism Development for the Wang Nam Khiao-Pha Khao Phu Lung Forest Reserve, Nakhon Ratchasima Province - อุดมวิทิต, สมหมาย (Journal of Applied Economics and Management Strategy, 2018)
การวิจัยครั้งนี้มุ่งวิเคราะห์ผลกระทบของการพัฒนาการท่องเที่ยวภายในพื้นที่ป่าสงวนแห่งชาติป่า วังน้ำเขียว-ป่าเขาภูหลวง จังหวัดนครราชสีมา โดยศึกษาผลกระทบทางด้านสังคมและสิ่งแวดล้อมต่อชุมชน ผ่านการสัมภาษณ์ครัวเรือนที่อาศัยอยู่ในพื้นที่ซึ่งเป็นผู้ได้รับผลกระทบโดยตรงจากการพัฒนาการท่องเที่ยวจำนวนทั้งสิ้น 157 ครัวเรือน ผลการศึกษาพบว่าผลของการพัฒนาการท่องเที่ยวได้ส่งผลกระทบต่อชุมชนในท้องถิ่น โดยผลกระทบมีทั้งด้านบวก ได้แก่ ทำให้ประชาชนในชุมชนได้รับผลประโยชน์ด้านรายได้ การลดลงของปัญหาการบุกรุกพื้นที่ป่า การกระจายรายได้ภายในชุมชนที่ดีขึ้น สำหรับผลกระทบทางด้านลบสะท้อนถึงความกังวลของกลุ่มตัวอย่างต่อปัญหาขยะ และราคาสินค้าอุปโภคบริโภคภายในชุมชนที่จะเพิ่มขึ้น ซึ่งการศึกษาครั้งนี้มีข้อเสนอแนะ คือ ภาครัฐควรส่งเสริมการมีส่วนร่วมของประชาชนในชุมชนในการบริหารจัดการการท่องเที่ยวเพื่อให้การพัฒนาการท่องเที่ยวไม่บิดเบือนวัฒนธรรม และความเป็นอยู่ของประชาชนในชุมชน และหน่วยงานที่เกี่ยวข้องในพื้นที่ควรมีการกำหนดมาตรการเพื่อรองรับ และแก้ไขปัญหาที่จะเกิดขึ้นจากการพัฒนาการท่องเที่ยว เช่น ปัญหาขยะ ปัญหาการบุกรุกพื้นที่ เป็นต้น This research aims to analyze impact on the community of the tourism development for the Wang Nam Khiao-Pha Khao Phu Lung Forest Reserve, Nakhon Ratchasima Province. The impact on the community of the tourism development consists of social site and environmental site. The research draws samples from households in Wang Nam Khaio collected by 157 questionnaires. The study results found that developed tourism has impacts on local communities, not only positive impacts which are increase in income, decrease of trespass forest area and better income distribution, but also negative impacts which are reflect to anxiety in garbage and price of goods in local communities. This study suggest that the government should promote the participation of communities in the tourism management to tourism development does not to change culture and being of the community and the relevant authorities in the region should be established to support the measures and solving problems will arise from the tourism Development such as wastrel problems Intrusion problems etc.